Skema Dana Non Halal Dalam Penetapan Denda Pembiayaan Bermasalah Pada Bank Muamalat - Nurul Setianingrum; Nur Hidayat; Dina Sabrinatus Soleha (ARBITRASE: Journal of Economics and Accounting, 2022)
The purpose of this research is to describe the concept of determining fines for non-performing financing at Bank Muamalat. Besides analyzing the implementation of the theory of fines for non-halal financing in non-halal funding schemes. There is a paradox among the public regarding the observance of Islamic banking in driving financial transactions in accordance with Islamic principles. It caused a low level of public knowledge of understanding the concept of Islamic banking. This debate arises when banking transactions are not completely in accordance with sharia principles (there are still elements of Riba, Gharar, and Maysir). Therefore customers' doubts arise in Islamic banking. This study uses a descriptive qualitative research method. The result of this study is the establishment of a fine policy at Bank Muamalat. It is intended for all customers who are not responsible for their financing installment obligations. The nominal fine adjusts the amount of financing proposed by the customer. The practice of setting fines is included in the category of non-halal funds but these funds are channeled back to the people in need through Baitul Maal Muamalat (BMM). This is in accordance with sharia, seen from the theory of non-halal funds in line with the MUI DSN rules and the hadith which states that the addition of debt is usury.